Analisis Efisiensi Hidrogen Peroksida Sebagai Bahan Tambahan Dalam Aerasi Untuk Mengurangi Pertumbuhan Filamentous Pada Air Limbah - Oris Hatpa Aditya Azhar; Naniek Ratni Juliardi A.R (Jurnal Serambi Engineering, 2024)
Overgrowth, also known as filamentous bacteria, is the abnormal growth of certain types of bacteria, such as Escherichia coli. The overgrowth of filamentous bacteria in activated sludge wastewater treatment plants has caused serious operational problems over the years. In addition, foaming problems caused by some filamentous bacteria can be a serious problem in all types of plants. The objectives of this study are to analyse the effective dose of hydrogen peroxide in aeration to suppress the growth of filamentous bacteria, to analyse the optimum length of time in which hydrogen peroxide is used in aeration to suppress the growth of filamentous bacteria, and to analyse the effect of the addition of hydrogen peroxide in aeration to suppress the growth of filamentous bacteria. The results of the study for the dose of hydrogen peroxide which is an effective dose is 3 ppm, because at a dose of 3 ppm can reduce MLSS levels by 59%, MLVSS by 64%, COD by 64% and BOD by 54%. The optimum period is 6 days with results of MLSS = 1764 mg/L, MLVSS = 910 mg/L, COD = 187 mg/L, BOD = 105 mg/L.